Change of Antioxidative Properties of Human Placental Extracts after Freezing - Rozanova, S. L.; Naumenko, E. I.; Rozanova, E. D.; Nardid, O. A. (Problems of Cryobiology and Cryomedicine, 2010)
The experimental data, obtained under comparative evaluation of different freeze-thawing protocols’ influence on human placenta extract antioxidant activity, estimated by capacity to reduce the ferric iron and ABTS+ radical, to chelate ferrous ions, to scavenge hydrogen peroxide and also by phenolic compound content, have been presented. Slow freezing of the extracts down to â€“20Â°Ð¡ has been shown to cause the lowering of its activity, while rapid freezing down to â€“196Â°Ð¡ increases the activity due to protein antioxidants’ conformational changes.